A rate dependent experimental and numerical analysis of adhesive joints under different loading directions - Lißner, Maria; Alabort, Enrique; Erice, Borja; Cui, Hao; Petrinic, Nik (Springer, 2018)
Adhesively bonded joints subjected to dynamic loading demand reliable and accurate measurement techniques to capture their rate dependent traction–separation behaviour. Particularly challenging is the measurement of damage and failure processes which are fundamental to develop the corresponding cohesive zone models. This paper proposes a new experimental methodology for the characterisation of rate-dependent behaviour of adhesive joints. The results of the adopted approach have been used to calibrate a rate-dependent numerical cohesive model proposed to simulate the failure of adhesive joints. The procedure was benchmarked against quasi-static DCB and ENF experiments.